Using The Inquiry Method To Improve Learning Outcomes Of Grade Vi Students At Sdn Girimekar 1 Cilengkrang On Environmental Care Material In Islamic Religious Education (PAI) Subject - Usep Suhendar; Udin Juhrodin (CV. AFDIFAL MAJU BERKAH, 2026)
Student learning outcomes in the topic of Environmental Care within Islamic Religious Education (PAI) for sixth-grade students at SDN Girimekar 1 Cilengkrang were initially low, with 71% of students scoring below the Minimum Mastery Criterion (KKM). This issue stemmed from the use of conventional teaching methods that positioned students as passive recipients of information, resulting in limited understanding and engagement. Based on the constructivist perspectives of Piaget, as well as the views of John Dewey and Ausubel, meaningful learning requires active involvement in questioning, investigating, and constructing knowledge. Therefore, this classroom action research (CAR) aims to improve student learning outcomes through the implementation of the inquiry method. The study was conducted in three cycles, each consisting of planning, action, observation, and reflection. The participants were 31 sixth-grade students. Data were collected through learning achievement tests, student activity observations, and field documentation. The findings show a significant improvement in students’ learning outcomes. Mastery learning increased from 29% in the pre-cycle to 39% in Cycle I, rose to 52% in Cycle II, and reached 72% in Cycle III. Additionally, students became more active and demonstrated improved behavior related to environmental care, such as reducing plastic waste, bringing personal tumblers, and disposing of waste properly. This research concludes that the inquiry method is effective in improving both cognitive learning outcomes and students’ environmental awareness in the Environmental Care topic of the PAI subject. Therefore, the inquiry method is recommended as an alternative learning approach to foster active, critical, and meaningful learning experiences.